The Art of Coming Upon Something - Behrisch, Tanya; Jardine, David (Art/Research International, 2024)
This paper explores the nature and experience of artistic mastery, that is, the experience of being long-practiced in an art such as writing, oil painting and teaching. Following the hermeneutic tradition and drawing on H.-G. Gadamer’s Truth and Method and other hermeneutic sources, the authors engage in a dialogue about their respective experiences of what it means to become experienced in an art form. The origin of their dialogue springs from one author reading and commenting on the other’s doctoral thesis, and discerning a hermeneutic sensibility in noticing the significance of emergent moments in life experience and in artistic practice.